This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have, f ( x ) = 4 x + 2 4 x
Now, f ( 1 − x ) = 4 1 − x + 2 4 1 − x = 4 + 2 ⋅ 4 x 4 ⇒ f ( 1 − x ) = 2 + 4 x 2 Now we observe a very nice property of the function from above which is, f ( x ) + f ( 1 − x ) = 1 ( w h y ) Now a sudden consequence of this implies, ⇒ f ( 9 9 9 1 ) + f ( 9 9 9 9 9 8 ) = 1 , f ( 9 9 9 2 ) + f ( 9 9 9 9 9 7 ) = 1 − − − f ( 9 9 9 4 9 9 ) + f ( 9 9 9 5 0 0 ) = 1 ⇒ k = 1 ∑ 9 9 8 f ( 9 9 9 k ) = 1 + 1 + + + ( 4 9 9 t e r m s ) = 4 9 9 Note that there are a class of functions that satisfy this property. The general form of such functions for integer a is: f ( x ) = a x + a a x